PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT KURABO MANUNGGAL TEXTILE INDUSTRIES KOTA TANGERANG - Sutedi, Aldi; Suroto (Journal of Research and Publication Innovation, 2024)
culture on employee performance at PT Kurabo Manunggal Textile Industries, both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 64 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient, coefficient of determination analysis and hypothesis testing. The results of this research are that the work environment has a significant effect on employee performance with the regression equation Y = 5.401 + 0.886X1, a correlation value of 0.803, meaning that the two variables have a very strong level of relationship. The coefficient of determination value is 64.5%. Hypothesis testing obtained tcount > ttable or (10.611 > 1.998). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant influence of the work environment on employee performance. Organizational culture has a significant effect on employee performance with the regression equation Y = 7.200 + 0.844 The coefficient of determination value is 42.5%. Hypothesis testing obtained tcount > ttable or (10.559 > 1.998). Thus, H0 is rejected. H2 is accepted, meaning that there is a significant influence of organizational culture on employee performance. The work environment and organizational culture have a significant effect on employee performance with the regression equation Y = 4.027 + 0.480X1 + 0.447X2. The correlation value is 0.831, meaning that the independent variable and the attachment variable have a very strong level of relationship. The coefficient of determination value is 69.0% while the remaining 31.0% is influenced by other factors.